1997
DOI: 10.1161/01.str.28.10.1908
|View full text |Cite
|
Sign up to set email alerts
|

Familial History of Stroke and Stroke Risk

Abstract: The increased risk of stroke among persons with a positive familial history of stroke compared with those without a familial history of stroke is consistent with the expression of genetic susceptibility, a shared environment, or both in the etiology of stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 12 publications
4
122
2
3
Order By: Relevance
“…Strong evidence for a genetic component in human stroke comes from twin and family studies (Brass et al, 1992;Bak et al, 2002;Liao et al, 1997). In a study of 300,000 subjects, risk factors such as smoking, a history of diabetes, hypertension, and coronary heart disease, did not alter stroke occurrence in people who had stroke events in previous generations of their family (Liao et al, 1997). Conflicting results regarding candidate gene studies for stroke emphasize the complexity of this multifactorial, complex disorder.…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…Strong evidence for a genetic component in human stroke comes from twin and family studies (Brass et al, 1992;Bak et al, 2002;Liao et al, 1997). In a study of 300,000 subjects, risk factors such as smoking, a history of diabetes, hypertension, and coronary heart disease, did not alter stroke occurrence in people who had stroke events in previous generations of their family (Liao et al, 1997). Conflicting results regarding candidate gene studies for stroke emphasize the complexity of this multifactorial, complex disorder.…”
Section: Genetic Aspects Of Stroke and Head Traumamentioning
confidence: 99%
“…Atherosclerosis is a multifactorial metabolic disorder that underlies various clinical cardiovascular diseases which are known to aggregate within families, such as coronary heart disease [1][2][3][4], myocardial infarction [2,3], and stroke [5]. Investigation of whether genetic factors influence a significant proportion of the interindividual variability in atherosclerosis is important in the search for susceptibility genes for these common disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been a decline in the incidence of stroke in the Western population during the past three decades (Heart Disease and Stroke Statistics-2003 Update, American Heart Association), the burden of this disease has increased and is expected to rise in the South Asian countries (Bulatao et al 1992). In various epidemiological studies in families (Jousilahti et al 1997;Liao et al 1997) and in twins (Brass et al 1992;Bak et al 2002), genetic factors were found to be involved in the predisposition of stroke in conjunction with the other risk factors.…”
Section: Introductionmentioning
confidence: 99%